2022
DOI: 10.1186/s13287-022-02777-4
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells and natural killer cells interaction mechanisms and potential clinical applications

Abstract: Natural killer cells (NK cells) are innate immune cells that are activated to fight tumor cells and virus-infected cells. NK cells also play an important role in the graft versus leukemia response. However, they can over-develop inflammatory reactions by secreting inflammatory cytokines and increasing Th1 differentiation, eventually leading to tissue damage. Today, researchers have attributed some autoimmune diseases and GVHD to NK cells. On the other hand, it has been shown that mesenchymal stem cells (MSCs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 173 publications
(271 reference statements)
0
16
0
Order By: Relevance
“…At lower doses, MSCs promoted NK cell formation and enhanced their antitumour activity against cancer cells, while at higher doses, MSCs inhibited NK cell formation and attenuated their tumour-killing effects [ 145 ]. A reasonable explanation for this dual immunomodulatory effect of MSCs on NK cells is that experimental conditions, including the MSC:NK cell ratio, cell concentration, quality of prestimulated NK cells, and coculture incubation time, affect the direction of interaction between MSCs and NK cells [ 138 , 146 ]. It has also been suggested that MSCs are inherently heterogeneous and simultaneously release proinflammatory cytokines and immune cell suppressive factors [ 147 ].…”
Section: Crosstalk Between Nk Cells and The Tmementioning
confidence: 99%
“…At lower doses, MSCs promoted NK cell formation and enhanced their antitumour activity against cancer cells, while at higher doses, MSCs inhibited NK cell formation and attenuated their tumour-killing effects [ 145 ]. A reasonable explanation for this dual immunomodulatory effect of MSCs on NK cells is that experimental conditions, including the MSC:NK cell ratio, cell concentration, quality of prestimulated NK cells, and coculture incubation time, affect the direction of interaction between MSCs and NK cells [ 138 , 146 ]. It has also been suggested that MSCs are inherently heterogeneous and simultaneously release proinflammatory cytokines and immune cell suppressive factors [ 147 ].…”
Section: Crosstalk Between Nk Cells and The Tmementioning
confidence: 99%
“…Granzyme B, a serine protease found in the lytic granules of NK cells, orchestrates cell apoptosis, especially through Bid (i.e., a Bcl-2 family member) ( 107 ). Interestingly, elevated levels of granzyme B have been shown to increase mesenchymal stem cell (MSC) populations ( 108 ). Conversely, MSCs suppress the activity of NK and other immune cells for example by increasing tryptophan metabolites ( 109 , 110 ).…”
Section: Secondary Effector Cells – From Natural Killer Cells To Mast...mentioning
confidence: 99%
“…In fact, the adhesion of MM cells to BM‐MSC upregulates cytokine secretion from both cell types, which in turn leads to the activation of major signalling pathways such as MEK‐ERK, JAK2/STAT3, PI3K and NF‐κβ. Downstream signalling targets include interleukin (IL)‐6, a well‐known potent driver of MM progression, as well as the immunosuppressive cytokines IL‐10 and transforming growth factor (TGF)‐β 8 …”
Section: Figurementioning
confidence: 99%
“…Downstream signalling targets include interleukin (IL)-6, a well-known potent driver of MM progression, as well as the immunosuppressive cytokines IL-10 and transforming growth factor (TGF)-β. 8 Interestingly, MM BM-MSC seems to play a more important role in NK cell exhaustion in the BM microenvironment than the malignant cells themselves. Several investigations have reported that IFN-γ secreted from activated NK cells induces the release of immunomodulatory factors (IDO1, TGF-β, HLA-G and PGE2) from BM-MSC, which in turn alter the expression of activation markers and ERK1/2 signalling in NK cells, hence modulating their cytotoxic activity.…”
mentioning
confidence: 99%